Association of Circulating MicroRNA-142-3p with Graves Disease - Rashad Ayad Al-Heety (College of Science for Women, University of Baghdad, 2021)
This study aims to investigate the possible role of circulating microRNA-142-3p (miR-142-3p) in the development of graves disease (GD) and its association with the antibody directed against thyroid stimulating hormone receptor (TSHR-Ab) production in patients with GD. Forty patients with positive TSHR-Ab enrolled in this study were divided ,based on treatment, into (22 untreated (newly diagnosed) and 18 treated patients) and based on family history (30 with positive family history and 10 with negative family history). In addition to forty healthy subjects with sex and age matching as a control group. The expression level of circulating miR-142-3p was determined by two steps reverse transcription polymerase chain reaction (RT-PCR) technique. Results show that there is a significant elevation (p < 0.01) in the expression of miR- 142-3p in the serum of both treated and untreated patients compared with controls and in patients with positive family history compared with negative family history. While its expression is non-significantly lower (P > 0.05) in the serum of treated patients compared with untreated ones. It has been found that miR- 142-3p expression was positively correlated with levels of TSHR-Ab, FT3, and FT4. In addition, the miR- 142-3p expression has a good diagnostic accuracy with sensitivity (82%) and specificity (80%). In conclusion, the differential expression of miR-142-3p between patients and healthy controls appears as a potential biomarker for diagnosis of GD and the positive correlation of miR-142-3p with TSHR-Ab suggesting the contribution of this miRNA in the development of GD.